Current approaches to the treatment of metastatic brain tumors - Nikolov, Vesna; Radisavljević, Miša; Jelenković, Boban; Stojanović, Nikola (Vojnosanitetski pregled, 2023)
Background/Aim. About 10% of patients diagnosed with systemic cancer had brain metastases in the central nervous system. Patients with diseased lungs, breasts, urinary and digestive tract, as well as melanoma of the skin, are increasingly treated by neurosurgeons due to their dissemination and creation of secondary deposits in the brain. The aim of the study was to assess the efficacy of treatment modalities for patients with brain metastasis according to their type – solitary or multiple, and also to the primary cancer site. Methods. The retrospective study was performed at the Clinic for Neurosurgery and the Clinic for Oncology from 2018 to 2020. One hundred and eleven patients with solitary changes in the brain and 122 patients with multiple changes were examined. Results. It was found that multiple metastases were more common in primary lung cancer, while single metastases were more common in adenocarcinoma. However, patients with primary adenocarcinoma died in a significantly higher number. Conclusion. Surgery and radiation remain the cornerstone of therapy for symptomatic lesions. We should strive to improve surgical techniques in the direction of less damage to the surrounding healthy tissue. Radiosurgery, as well as whole brain radiotherapy, remains the basic form in the treatment of multiple metastases.